A Synergistic action towards a policy of reproductive rights: a neverending story - Negrão, Telia (Saúde e Sociedade, 2012)
In Brazil, reproductive rights are provided for a national legislation and regulations of the Ministry of Health, should be the object of public policy, and is an agenda of women's movement since 1970 decade. Family planning integrates these policies, based on the principles of non-coercion, informed choice and responsible, resulting in ethical standards. The health council of Porto Alegre, a mechanism established by law to exercise social control over those policies, was asked in 2006 to ensure the ethical and legal parameters when a program of hormone implants in adolescents has been authorized by the city without a debate in the Council. The purpose of this paper is to discuss, from the Political Science and Feminist Theory the strategies used by the feminist movement for the reversal of this program, its alliances and arguments, as well as lessons learned. As a result is has obtained the reversal of the implants program and the deliberative body of the Health Council on health public policy.